New sports, COVID-19 and the heat: sports injuries and illnesses in the Tokyo 2020 Summer Olympics - Soligard, T.; Palmer, D.; Steffen, K.; Dias Lopes, A.; Grek, N.; Onishi, K.; Shimakawa, T.; Grant, M.-E.; Mountjoy, M.; Budgett, R.; Engebretsen, L. (British Journal of Sports Medicine, 2022)
Objective: To describe the incidence of injuries and illnesses sustained during the Tokyo Summer Olympic Games from 23 July to 8 August 2021.